Nahwu Learning at Darul Ikhlas Islamic Boarding School Mandailing Natal - Nur Padilah Nasution (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The researcher chose this topic because in the first observation, the researcher found that the teacher only used one method, and many students were skilled at reading books, and some graduates were able to study in the Middle East, from the results of teaching grammar.how is nahwu learning at the Darul Ikhlas Dalan Islamic boarding school Leading Mandaeling Natal? The purpose of this research is to reveal the teaching of grammar in terms of the objectives, materials, methods and means of teaching nahwu and its evaluation. This research Is based on field research using a descriptive methodology. The tools to collect i formation are observation, interviews and documentation. After researched about teaching grammar in this institution, he concluded that the purpose of teaching grammar in this institution is fo rstudents to be able to read and translate Arabic texts. And able to parse correct Arabic sentences. The grammar teaching material in semester 2 at Darul Ikhlas Islamic boarding schoo lDalan Lidang Mandaling Natel is very short written by Mr. Ahmed Zainy Dahlan consisting of speech, syntax, knowing the signs, nominative nouns, accusative nouns, and subjunctive nouns. The method of teaching grammar at the Darul Ikhlas Islamic Boarding School Leading Mandailing Nattal is the standard method. And the facilities used are visual aids such as whiteboards and image data. And evaluation of grammar education at the Dar Al-Ikhlas Institute